Cancer-associated fibroblasts: multidimensional players in liver cancer - Pan, Yanyun; Qiu, Yuangang; Zhou, Xinbin; Mao, Wei; Xu, Xiaoming (Frontiers in Oncology, 2025)
Cancer-associated fibroblasts (CAFs), the most abundant stromal cells in the tumor microenvironment (TME), control tumor growth through production and organization of the extracellular matrix (ECM) for a long time. However, the results from different studies that have focused on targeting CAFs to disturb tumor progression are extremely controversial. Recent studies using advanced single-cell RNA sequencing technology (scRNAseq) combined with multiple genetically engineered mouse models have identified diverse CAF subpopulations in the premalignant liver microenvironment (PME) of hepatocellular carcinoma (HCC) and TME of intrahepatic cholangiocarcinoma (ICC), providing a deeper understanding of the exact roles of each CAF subpopulation in cancer development. This review focuses on the specific protein markers, signaling pathways, and functions of various emerging CAF subclusters that contribute to the development of ICC and HCC. Elucidating the role and regulation of CAF subpopulations under different pathophysiological conditions will facilitate the discovery of new therapeutics that modulate CAF activity.